A morphological study of variations in superficial palmar arches of the hand - Chandni Gupta; Sneha Guruprasad Kalthur; Narga Nair; Shakuntala R Pai (Wolters Kluwer Medknow Publications, 2015)
Objectives: Arterial arches of the hand are very important for orthopedic surgeons as well as microvascular surgeons while doing surgeries on hand. The greatest risk associated with harvesting the radial artery for coronary artery bypass grafting is ischemia of the soft tissues of the hand. There may be numerous variations in the formation of these arterial arches which will be important for the surgeons. So, for the above-mentioned reasons the following study was undertaken to look for the pattern of superficial arches in hands and its variations. Materials and Methods: The study was done on 75 formalin fixed upper limbs from the Department of Anatomy. Incision was given according to Cunningham manual of anatomy and superficial palmar arch was exposed, and its formation from different branches was noted down. The variations were noted down in the formation of superficial palmar arch to provide a database of the normal and variant anatomy. Results: In 77.3% of specimens superficial palmar arch was complete and in 22.6% of specimens it was incomplete. Conclusion: The variations found in this study will help not only the anatomists, but also orthopedics and microvascular surgeons who do surgery on hands. Current progress in the microsurgical procedures for reconstructive hand operations needs the understanding of variant arterial arches, the comprehensive knowledge of which is vital for the surgical interventions and successful outcome of the surgeries.